Effect of head size and rotation on taper corrosion in a hip simulator - Christian M. Wight (The British Editorial Society of Bone & Joint Surgery, 2021)
Aims: This study investigates head-neck taper corrosion with varying head size in a novel hip simulator instrumented to measure corrosion related electrical activity under torsional loads. Methods: In all, six 28 mm and six 36 mm titanium stem-cobalt chrome head pairs with polyethylene sockets were tested in a novel instrumented hip simulator. Samples were tested using simulated gait data with incremental increasing loads to determine corrosion onset load and electrochemical activity. Half of each head size group were then cycled with simulated gait and the other half with gait compression only. Damage was measured by area and maximum linear wear depth. Results: Overall, 36 mm heads had lower corrosion onset load (p = 0.009) and change in open circuit potential (OCP) during simulated gait with (p = 0.006) and without joint movement (p = 0.004). Discontinuing gait’s joint movement decreased corrosion currents (p = 0.042); however, wear testing showed no significant effect of joint movement on taper damage. In addition, 36 mm heads had greater corrosion area (p = 0.050), but no significant difference was found for maximum linear wear depth (p = 0.155). Conclusion: Larger heads are more susceptible to taper corrosion; however, not due to frictional torque as hypothesized. An alternative hypothesis of taper flexural rigidity differential is proposed. Further studies are necessary to investigate the clinical significance and underlying mechanism of this finding. Cite this article: Bone Jt Open 2021;2(11):1004–1016.